Organization of projection neurons and local neurons of the primary auditory center in the fruit fly Drosophila melanogaster. Issue 6 (19th January 2016) - Matsuo, Eriko; Seki, Haruyoshi; Asai, Tomonori; Morimoto, Takako; Miyakawa, Hiroyoshi; Ito, Kei; Kamikouchi, Azusa
ABSTRACT: Acoustic communication between insects serves as an excellent model system for analyzing the neuronal mechanisms underlying auditory information processing. The detailed organization of auditory neural circuits in the brain has not yet been described. To understand the central auditory pathways, we used the brain of the fruit fly Drosophila melanogaster as a model and performed a large‐scale analysis of the interneurons associated with the primary auditory center. By screening expression driver strains and performing single‐cell labeling of these strains, we identified 44 types of interneurons innervating the primary auditory center. Five types were local interneurons whereas the other 39 types were projection interneurons connecting the primary auditory center with other brain regions. The projection neurons comprised three frequency‐selective pathways and two frequency‐embracive pathways. Mapping of their connection targets revealed that five neuropils in the brain—the wedge (WED), anterior ventrolateral protocerebrum, posterior ventrolateral protocerebrum (PVLP), saddle (SAD), and gnathal ganglia (GNG)—were intensively connected with the primary auditory center. In addition, several other neuropils, including visual and olfactory centers in the brain, were directly connected to the primary auditory center. The distribution patterns of the spines and boutons of the identified neurons suggest that auditory information is sent mainly from the primary auditory center to the PVLP, WED, SAD, GNG, and thoracico‐abdominal ganglia. Based on these findings, we established the first comprehensive map of secondary auditory interneurons, which indicates the downstream information flow to parallel ascending pathways, multimodal pathways, and descending pathways. J. Comp. Neurol. 524:1099–1164, 2016. © 2016 Wiley Periodicals, Inc. Abstract : Using the flip‐out technique and confocal microscopy, the authors establish an atlas of projection neurons and local neurons downstream of the primary auditory center in the fly brain at the single‐neuron resolution. The second‐order auditory neural circuits comprise parallel ascending pathways, multimodal pathways, and descending pathways.